Implementation Of Health Innovations For Patients With Kyphos Through Therapy Jacket Registered Patent And Copyright - Aldi Adi Pratama; Aprilia Tri Purwandari (Universitas Trunojoyo Madura, 2023)
This activity is intended to provide an alternative healing through Therapy Jackets which were previously the result of an innovative 2021 student creativity program. The main problem faced by patients is severe pain when they want to stand up from a sitting position. The results of these products are used in advanced community service, by conducting therapeutic trials on two yield patients, with the aim of reducing the degree of bending in one month. The first patient experienced a decrease in the degree of bending on the fifth to eighth day of therapy from 36° and experienced a change on the fifth day with a value of 35.6°. Subsequent changes occurred on the sixth day 35.5°, seventh 35° and eighth 34.9°. The second patient experienced a decrease in the degree of bending on the fifth to sixth day of therapy from a bending value of 38°, and experienced a change on the fifth day with a value of 37°. Subsequent changes occurred on the sixth to the eighth day 36.7°. This product has also been filed for patent registration with application number S00202106605 and copyright registration with registration number 000266965.